2017
DOI: 10.1016/j.archoralbio.2016.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-Alpha stimulates cytokine expression and transient sensitization of trigeminal nociceptive neurons

Abstract: Objective Elevated levels of tumor necrosis factor-alpha (TNF-α) in the capsule of the temporomandibular joint (TMJ) are implicated in the underlying pathology of temporomandibular disorders (TMD). TMD are a group of conditions that result in pain in the TMJ and/or muscles of mastication, and are associated with significant social and economic burdens. The goal of this study was to investigate the effect of elevated TNF-α levels in the TMJ capsule on nocifensive behavioral response to mechanical stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Other studies have shown that CGRP released from TG neurons stimulate production of tumor necrosis factor‐α (TNF‐α) in satellite cells, which then acts on TG neurons to increase both the production and the release of CGRP . Moreover, TNF‐α can acutely sensitize TG neurons directly, as well as evoke the upregulation of several proinflammatory cytokines in these neurons, likely through the TNF‐α receptors . Together, these studies demonstrate that CGRP secreted from TG neurons can increase cytokine production in TG neurons and satellite glial cells and increase its own production and release from neurons, maintaining a sensitized state and enhancing pain …”
Section: Role Of Trigeminal Cgrp In Migraine – Preclinical Evidencementioning
confidence: 81%
See 3 more Smart Citations
“…Other studies have shown that CGRP released from TG neurons stimulate production of tumor necrosis factor‐α (TNF‐α) in satellite cells, which then acts on TG neurons to increase both the production and the release of CGRP . Moreover, TNF‐α can acutely sensitize TG neurons directly, as well as evoke the upregulation of several proinflammatory cytokines in these neurons, likely through the TNF‐α receptors . Together, these studies demonstrate that CGRP secreted from TG neurons can increase cytokine production in TG neurons and satellite glial cells and increase its own production and release from neurons, maintaining a sensitized state and enhancing pain …”
Section: Role Of Trigeminal Cgrp In Migraine – Preclinical Evidencementioning
confidence: 81%
“…Moreover, TNF‐α can acutely sensitize TG neurons directly, as well as evoke the upregulation of several proinflammatory cytokines in these neurons, likely through the TNF‐α receptors . Together, these studies demonstrate that CGRP secreted from TG neurons can increase cytokine production in TG neurons and satellite glial cells and increase its own production and release from neurons, maintaining a sensitized state and enhancing pain …”
Section: Role Of Trigeminal Cgrp In Migraine – Preclinical Evidencementioning
confidence: 81%
See 2 more Smart Citations
“…Our method was adapted from the 'rat von Frey test method', which has been previously published. 7,54,55 Briefly, before the test, the mice were housed in a special plastic cage, with a slight gap in the middle, for 30 min on 3 consecutive days for acclimation. Then, the orofacial areas directly overlaying the TMJ were carefully shaved under anaesthesia, avoiding the whiskers, 1 day before the starting date of the testing session.…”
Section: Histology Analysismentioning
confidence: 99%